La psychagogie comme mode d’accompagnement - Raymond Laprée; Suzanne Blouin (Éducation et Socialisation)
The psychagogy of values is a way of accompanying the other on the path towards oneself, by the means of a symbolic experience. Can it be appropriate for children from 6 to 11 years ? Fifteen young volunteers, whose one typical case is more completely documented, agreed to engage in this experience. The results of this experiment, discussed from the standpoint of the symbolic effectiveness, raise finally questions as for certain aspects of the definition of the ‟spiritual lifeˮ suggested by the System of Education of Quebec (Canada) to ‟support the blooming of the pupilˮ.